2007
DOI: 10.1520/jte100922
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Fatigue Resistance of HVOF Thermal Spray WC-CoCr Coatings by Means of Impact Testing

Abstract: Impact testing is an efficient experimental procedure that enables the determination of the fatigue resistance of mono- and multi-layer coatings deposited on various substrates, which was not possible with the common testing methods previously available. In this paper an advanced impact tester, able to assess the fatigue failure resistance of coatings working under cyclic loading conditions, is presented. The fatigue failure of the tested coatings was determined by means of scanning electron, optical microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They showed that the multilayer coatings presented a microstructure composed of alternate phases of chromium carbide cermet and oxides, which were resulted from preferential oxidation of chromium compounds. The mechanical properties of mono and multilayered coatings were examined by David et al [6]. They observed that WC-CoCr deposited by HVOF spraying onto P91 steel presented on high fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the multilayer coatings presented a microstructure composed of alternate phases of chromium carbide cermet and oxides, which were resulted from preferential oxidation of chromium compounds. The mechanical properties of mono and multilayered coatings were examined by David et al [6]. They observed that WC-CoCr deposited by HVOF spraying onto P91 steel presented on high fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%